Stock selling during takeovers - Ordóñez-Calafí, Guillem; Thanassoulis, John (Journal of Corporate Finance, 2020)
Stock sales during takeover negotiations weaken the target board's ability to recommend against the takeover, i.e., to resist. Sophisticated shareholders therefore face a coordination problem when deciding whether to sell-out early; and their actions generate a feedback loop between trading volumes and takeover outcomes. Bidding firms, anticipating the pressurising effect of future share sales on the target board, may reduce their bids. We study these tensions theoretically. We find that increasing the influence of shareholders during the bidding process lowers equilibrium bids; elongates the bidding process; but raises the overall probability of bid acceptance; and raises expected premia for unsophisticated shareholders.